PERBEDAAN PENGARUH LATIHAN HANDSTAND PUSH-UP DAN FLOOR PUSH-UP TERHADAP DAYA TAHAN OTOT LENGAN ATLET GULAT PUTRA JAWA TENGAH TAHUN 2020 - Ade Mulyono; Rima Febrianti; Satrio Sakti Rumpoko (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2021)
This research is an experimental research. This research was conducted using quantitative descriptions and using "Two group pretest-posttest design". The subjects of this study were wrestling athletes of Central Java Province who trained at the Han Academy Solo Club, totaling 30 athletes, consisting of 15 athletes for Handstand Push-up treatment and 15 athletes for Floor Push-up treatment. Sources of data in this study came from 30 athletes. The data collection technique is through a push-up test to measure the endurance of the arm muscles. Data analysis used the Wilcoxon nonparametric statistical test. The results of data analysis can be presented as follows: The results of the increasing test for Handstand push-ups obtained an from 46,46 to 73 and the results of the increase for Floor Push-ups obtained an from 45 to 61,26. Which means that there is a significant improvement to the exercise program. So it can be concluded that the Handstand Push-up treatment is better than the Floor Push-up treatment to increase the endurance of the arm muscles of male wrestling athletes in Central Java in 2020 by comparing the pre test and post test.